(untitled) (Research, Society and Development, 2020)
Day cares centers and pre-schools share caring with the family, which is fundamental to the child’s development. However, it was up to this professional to build and consolidate this identity, understanding that early childhood education is not just drawing and playing, it is serious work, which demands care, knowledge and commitment to work. This time, a research was carried out in the municipal education network in the city of Itaúna-MG and São Miguel das Matas-BA with early childhood teachers, in which it was sought to highlight the training of professionals and their constitution, the identity of teachers belonging to the network and, mainly, the practice of the teacher of early childhood education in order to know and understand the working relationship of these professionals. The results indicate that early childhood teachers are advancing in the construction of their identity, investing in training and professional qualification, but the practice still presents several difficulties, mainly regarding inclusion.